Impact of CSR regulation strengthening on corporate spending patterns: A ten-year Indian Analysis - Mehta, Shital; Patil, Harshali; Kukreja, C A Muskkan (The International tax journal, 2026)
This study examines the role of recent regulatory changes on corporate governance and the role of CSR spending in shaping investments in both areas among firms, the new Board Governance Mandates (BGM) related to the composition of board members specific to India, and the amended Corporate Social Responsibility Regulation Act. It is focused on the ten years after the implementation of Section 135 of the Companies Act, 2013, requiring firms to engage in mandatory CSR outlay once certain thresholds are met. Expenditure data is available at the aggregate level for the top ten Indian companies annually per year from 2014–15 to 2023–24. Research links two major policy interventions, the mandatory CSR spend and the requirement for listed and large companies to appoint at least one independent woman director. It analyses these reforms together to determine whether improvements in board governance and greater board diversity draw CSR expenditures away from the traditional model. Using 5,348 project-level observations drawn from company-specific CSR data files, the paper first applies a pre–post analytical design around the 2019 governance inflection point. It then extends the descriptive analysis with a two-way fixed-effects specification, as reported in the source research.